RISK DETERMINANTS AND PREVENTIVE APPROACHES FOR POST-CHOLECYSTECTOMY BILIARY COMPLICATIONS IN THE EARLY POSTOPERATIVE PERIOD - A.U. Abdusamatov; D.Sh. Abdurakhmonov (Scholar Express Journals, 2025)
Cholecystectomy is one of the most common surgical operations in global practice, with more than 1.5 million procedures performed annually. Despite the introduction of minimally invasive technologies and standardization of surgical techniques, the frequency of early biliary complications remains at 0.2-2.7%, representing a serious clinical problem. These complications not only worsen immediate treatment results but can also lead to the formation of persistent bile duct dysfunctions, significantly reducing patients' quality of life.The spectrum of early biliary complications includes bile leakage, injuries to the main bile ducts of varying severity, cystic duct stump insufficiency, biliary peritonitis, and biloma formation. The pathogenesis of these complications is multifactorial, including both anatomical predispositions and technical aspects of the operation.
Keywords: Cholecystectomy; biliary complications; bile leakage